2017
DOI: 10.22159/ajpcr.2017.v10i3.16205
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Optimization and Characterization of Ganciclovir Loaded Dry Chitosan Nanoparticles

Abstract: Objective: The objective of this work was to formulate, optimize, and characterize ganciclovir (GCV) loaded dry chitosan nanoparticles (CSNPs). Methods:The GCV loaded CSNPs was prepared by ionic gelation method. Box-Behnken design was employed to optimize the influence of independent process and formulation variables like drug to polymer ratio, concentration of sodium tripolyphosphate, and stirring time (min) on the dependent variables such as particle size (PS) and drug encapsulation efficiency (% EE). The op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
(16 reference statements)
2
4
0
Order By: Relevance
“…Under these conditions, the absorption of water inside the CS polymer network leads to swelling, and therefore the particle sizes will be larger than the actual value. These differences were also reported by Patel et al 58 …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Under these conditions, the absorption of water inside the CS polymer network leads to swelling, and therefore the particle sizes will be larger than the actual value. These differences were also reported by Patel et al 58 …”
Section: Resultssupporting
confidence: 86%
“…Under these conditions, the absorption of water inside the CS polymer network leads to swelling, and therefore the particle sizes will be larger than the actual value. These differences were also reported by Patel et al 58 Furthermore, stability analysis results for lipid-coated nanoparticles showed a size enhancement about 4% by changing the size of nanoparticles from 301 to 314 nm after 1 month. However, zeta potential was changed to −34.1 mV after 1 month.…”
Section: Characterization Resultssupporting
confidence: 70%
“…The dispersion of prepared transethosome (100 µL) was diluted to a volume of 2 mL using Milli-Q water. The diluted sample was then transferred into disposable polystyrene cuvettes and subsequently inserted into the Zeta sizer and measured [46].…”
Section: Optimization Of Transethosomesmentioning
confidence: 99%
“…Entrapment efficiency was determined by determining levels of free diltiazem HCl in the supernatant using a UV-Vis spectrophotometer at the maximum wavelength (236 nm) [16]. The calculation of entrapment efficiency using the following equation 1.…”
Section: Entrapment Efficiencymentioning
confidence: 99%